Project Topic Solving Problem Supply Chain In Micro Small And Medium Enterprises With Supply Chain Management - Ala’ Odeh; Edo Habib Maulana (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
Supply Chain Management (SCM) is the management of a supply chain activities to maximize customer value and achieve a sustainable competitive advantage. It acts as a strategic competitive tool for the micro small and medium enterprises that made the issue of logistics as a strategy to compete to be able to win the market competition. The purpose of this paper is to analyze the effectiveness of the Supply Chain Management implemented by a micro small and medium enterprises in Indonesia. The results then will be advised to the owner to improve the existing supply chain management.